An evaluation of the performance of the ARB Apex Bank on rural banks in Ashanti: the case of Atwima Kwanwoma Rural Bank Ltd. - Gyamfi, Lovia Owusu (2011)
A thesis submitted to the College of Arts and Social Sciences, KNUST School of Business, 2008